Editorial: eHealth literacy: Emergence of a new concept for creating, evaluating and understanding online health resources for the public - Andre W. Kushniruk (ACMI Fellow; CAHS Fellow) (Knowledge Management & E-Learning: An International Journal, 2015)
The ability of consumers of health information to effectively understand, process and apply health information presented to them is a critical factor in improving health knowledge and developing effective health promotion strategies. Nowhere has this become more apparent than in efforts to apply information technology in the development of a range of systems and applications targeted for use by patients, and the general population. Indeed, success and failure of eHealth initiatives has been shown to depend on consideration of how to effectively design and deploy health information to consumers. Health literacy has become an important area of study that focuses on studying how health information can be understood and applied to improve health. In recent years the concept of eHealth literacy has also emerged, that sits at the intersection of health literacy and information technology literacy. In this special issue, a range of papers are presented that focus on the emerging concept of eHealth literacy. The papers in the special issue focus on basic definitional and conceptual issues as well as methodological approaches to studying health and eHealth literacy. A special focus of the issue is on how these concepts apply and can be adapted for improving health information technologies and applications.